2019
DOI: 10.1186/s11671-019-3057-0
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin-Loaded PEGylated Liposomes: Antitumor Efficacy, Acute Toxicity, and Tissue Distribution

Abstract: Bufalin, derived from Venenum Bufonis , exerts antitumor effects but has low bioavailability and adverse effects when administered as a single agent. The purpose of this study was to evaluate the physical and chemical properties, antitumor efficacy, general pharmacology, acute toxicity, and tissue distribution profile of bufalin-loaded PEGylated liposomes (BF/PEG-LP), which were prepared in a previous study. To evaluate the safety of the preparation, a red blood cell hemolysis test was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…However, high concentrations of MuA-loaded GA liposomes results in decreasing thecell viability, where the concentration of 100 µM would reduce the cell viability to only 20%. This result shows the excellent performance of MuA-loaded GA liposomes, as compared to some other synthetic liposomes which is in close agreement with previous studies where the required concentrations of co-encapsulated nano-liposomes and and bufalin-loaded PEGylated Liposomes were 500 µM and 200 µM, respectively [34,35].…”
Section: Cell Viability (3d): Cancer Spheroidsupporting
confidence: 92%
See 1 more Smart Citation
“…However, high concentrations of MuA-loaded GA liposomes results in decreasing thecell viability, where the concentration of 100 µM would reduce the cell viability to only 20%. This result shows the excellent performance of MuA-loaded GA liposomes, as compared to some other synthetic liposomes which is in close agreement with previous studies where the required concentrations of co-encapsulated nano-liposomes and and bufalin-loaded PEGylated Liposomes were 500 µM and 200 µM, respectively [34,35].…”
Section: Cell Viability (3d): Cancer Spheroidsupporting
confidence: 92%
“…There are currently many methods for liver cancer therapy such as transplant, surgical resection, stereotactic body radiation therapy, and chemotherapy. However, chemotherapy with an advance of target therapy remains a synergistic treatment option [ 35 ]. Target therapy is an approach that used a molecularly targeted drug delivery systems of nanoparticles, nucleic acids, peptides, and proteins to encapsulate the small molecular drug for disease treatment [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that bufalin as one of the main active ingredients of toad venom, has a killing effect on a variety of tumor cells, and combination of bufalin with 5-urouracial can improve the drug resistance of tumor cells, reduce proliferation and induce apoptosis [17,18] . The previous studies found that bufalin and its liposome could induce apoptosis of HepG2, HCT116, A549 and U251 cells in vitro, and inhibit the growth of nude mouse xenograft gliomas in vivo [19,20] . In present study, the possible molecular mechanisms of bufalin how to inducing mitochondrial dysfunction to promote apoptosis in gliomas cells were elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that bufalin, one of the main active compounds in toad venom, has a killing effect on a variety of tumour cells, and the combination of bufalin with 5-fluorouracil can attenuate the drug resistance of tumour cells, reduce their proliferation and induce their apoptosis [ 17 , 18 ]. Previous studies showed that bufalin and related liposomes can induce the apoptosis of HepG2, HCT116, A549 and U251 cells in vitro and inhibit the growth of nude mouse xenograft gliomas in vivo [ 19 , 20 ]. In the present study, the possible molecular mechanisms by which bufalin induces mitochondrial dysfunction to promote the apoptosis of glioma cells were elucidated.…”
Section: Discussionmentioning
confidence: 99%